Studies on the use of hollow fibre membrane bioreactors for tissue generation by using rat bone marrow fibroblastic cells and a composite scaffold. - Ye, H; Xia, Z; Ferguson, D; Triffitt, J; Cui, Z (2007)
Production of sufficient tissue in vitro for use in tissue engineering is limited mainly by the absence of adequate oxygenation and appropriate transport of nutrients to, and waste product from, the tissue. To overcome the limitations of diffusive transport, the possibility of growing three dimensional (3D) tissue structures by using hollow fibre membrane bioreactors (HFMB) has been considered in this study. The hollow fibre membranes, embedded in the 3D scaffold, are porous and semi-permeable and can thus serve similar functions to arteries and veins in vivo. Collagen gel and Cytodex 1 microcarriers were used as a composite 3D scaffold and permeating cellulose acetate hollow fibre membranes were attached to both ends of a polycarbonate cylindrical shell to form a bioreactor. Rat bone marrow fibroblastic (RBMF) cells were seeded initially onto Cytodex 1 microcarriers and these were subsequently mixed with collagen gel before inoculation into the bioreactor. Bioreactors were perfused by culture medium through the hollow fibre membranes for a one week period. Bioreactors containing cells cultured under similar conditions except for the lack of perfusion of medium served as controls. The proliferation, viability, metabolism and morphological appearances of the cells in the perfused and non-perfused constructs were compared. The results indicated that there was significantly greater maintenance of functional activity and normal cellular morphology in the perfused group than in the non-perfused group. Further studies are required to evaluate the additional advantages of using this novel HFMB for growing 3D dense tissues.